2020
DOI: 10.1177/0890117120958545
|View full text |Cite
|
Sign up to set email alerts
|

Better Me Within Randomized Trial: Faith-Based Diabetes Prevention Program for Weight Loss in African American Women

Abstract: Purpose: Previous DPP translations in African American women have been suboptimal. This trial evaluated a community-based participatory research developed faith-based diabetes prevention program (DPP) to improve weight loss in African American women. Design: This cluster randomized trial allocated churches to faith-based (FDPP) or standard (SDPP) DPP interventions. Setting. African American churches. Subjects. Eleven churches with 221 African American women (aged 48.8 ± 11.2 years, BMI = 36.7 ± 8.4) received t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…CONSORT diagram of community-based DPP trial. The figure was adopted from the Better Me Within trial [38].…”
Section: Study Limitationsmentioning
confidence: 99%
“…CONSORT diagram of community-based DPP trial. The figure was adopted from the Better Me Within trial [38].…”
Section: Study Limitationsmentioning
confidence: 99%
“…Consistent with the findings from our heart disease risk reduction programme, we combined faith‐based components—including active church leader support—into the standard DPP curriculum. Participants in the programme who were followed for 10 months had significant improvements in weight loss, health behaviours, and biometrics 69 . The study is very important for several reasons.…”
Section: Applying a National Best‐practice Model In The Local Community Context—testing The Diabetes Prevention Program On Reducing Weighmentioning
confidence: 99%
“…Thus, a faith‐based version of the DPP has the potential to help African‐American women reach 5% weight loss in a community‐setting outside of the AHC. Further, the programme demonstrated that female African‐American congregation members can successfully deliver the DPP providing a potential pathway for increasing reach and adoption into high‐risk communities 69 …”
Section: Applying a National Best‐practice Model In The Local Community Context—testing The Diabetes Prevention Program On Reducing Weighmentioning
confidence: 99%
See 2 more Smart Citations